Pengaruh Brand Awareness dan Service Quality terhadap Repurchase Intention Konsumen Rocket Chicken Veteran Marabahan Kabupaten Barito Kuala - Samsul Arifin; Rusniati Rusniati; Ikhwan Faisal; Mohammad Yudy Rachman; Sudirwo Sudirwo (Journal of Management and Business, 2025)
This research was conducted to analyze the influence of brand awareness and service quality both partially and simultaneously on the repurchase intention of Rocket Chicken Veteran Marabahan consumers. The population in this study is the people of Marabahan with a sample size of 100 respondents. The sampling technique used is purposive sampling. Data analysis used multiple linear regression analysis. The research results show that partially, brand awareness and service quality have a positive and significant effect on repurchase intention. Simultaneously, brand awareness and service quality also have a positive and significant impact on the repurchase intention of Rocket Chicken Veteran Marabahan consumers. However, the company needs to continuously expand its reach through various promotional media, build trust with both old and new customers, and provide the best service to meet consumer needs.